Understanding the formation mechanism of consumers’ behavioral intention on Double 11 shopping carnival: Integrating S-O-R and ELM theories - Shiau, Wen-Lung; Zhou, Mengru; Liu, Chang (Frontiers in Psychology, 2022)
Double 11 shopping carnival, celebrated by the most successful electronic-commerce (e-commerce) Chinese company, Alibaba, has always been the online shopping festival with the highest turnover and has the largest number of consumers and enterprises in China. This study integrates the elaboration likelihood model (ELM) and stimulus-organism-response (S-O-R) theory to study the dual-processing path of information, which drives customers’ behavioral intention on Double 11. There are 454 valid samples of data are collected, and the research model is tested using the partial least squares method. Results show that in the Double 11 context, two different processing mechanisms affect consumers’ behavioral intention. Thereinto, consumers’ behavioral intention is more affected by the peripheral path than the central path. The affective experience affected by the information stimulus has a greater impact on the behavioral intention than cognitive experience. Furthermore, we find situational involvement has different moderating effects on the relationship between two experiences and behavioral intention.